Strategy for Increasing The Skilled Human Resources Through Training in Creating The Bridal Delivery - Setyowati, Erna; Maghfiroh, Anik; Naam, Muh Fakhrihun (Universitas Negeri Semarang, 2023)
The objective of implementing this community service is to increase the knowledge and skills of the PKK women in the community sub-district of Karanganyar Gunung , Semarang in making the bridal delivery. The methods chosen to carry out this community service are as follows: 1) lectures and questions-answers are used when giving material about the bridal delivery . The practice method is used when the trainer or the presenter practices the steps for making the bridal delivery, then the training participants are asked to practice making the bridal delivery which has already been practiced, with the guidance of the trainer and the community service team. 3) monitoring and evaluation. The community service activities that have been carried out run smoothly and successfully without any obstacles. This can be seen from the enthusiasm of the participants who feel that they have increased their knowledge and skills in making the bridal deliveries. Besides that, the bridal delivery training also received a positive response from all the training participants. This can be seen from the seriousness, earnestness and activeness of the participants when participating in the bridal delivery training.